Biochemical and Serological Investigations in Incidentally Detected Asymptomatic HBsAg-Positive Subjects (IDAHS) (Community Based Medical Journal, 2025)
This cross-sectional, observational study was conducted among 50 incidentally detected asymptomatic HBsAg positive subjects (IDAHS) in the out-patient department (OPD) of the Department of Hepatology, Shaheed Suhrawardy Medical College Hospital, Dhaka, Bangladesh, between May and November of 2017. All demographic characters like age, sex, education level, occupation and socio-economic status as well as mode of detection and duration of HBsAg positivity and risk factors were documented in the data sheet. Serum bilirubin and alanine aminotransferase (ALT) were measured using auto analyzer in the biochemistry laboratory. Serum bilirubin ≤1.0 mg/dl and ALT levels ≤40 IU/L in males and ≤30 IU/L in females were set as normal. Serological tests were performed by using ELISA method, e.g., HBeAg and anti-HBeAg in the microbiology laboratory. The participants’ age ranged between 21 and 57 years with a mean of 30.2±9.3 years. We found that 23(46%) subjects were detected HBsAg positive during routine checkup followed by blood donation 11(22%), antenatal check-up 7(14%), going abroad 4(8%), family screening 3(6%) and before vaccination in 2(4%) subjects respectively. Among risk factors, 18(36%) had family history of HBsAg and only 1(2%) subject had unsafe sexual exposure. In total, 17(34%) were found having elevated ALT levels and only 1(2%) had abnormal bilirubin level. In total, 38(76%) subjects were HBeAg negative, while 35(70%) were Anti-HBe positive. Most IDAHS subjects were negative to HBeAg, however, they need to be followed up at regular intervals so that appropriate measures can be taken in time.  CBMJ 2025 January: Vol. 14 No. 01 P: 16-21